Iconology, visual culture and media aestetics - Mitchell, William John Thomas (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article contains fragments of three chapters form the book Image Science. Iconology, Visual Culture and Media Aesthetics (Chicago 2015), titled The are no Visual Media , Back to the Drawing Board and Foundational Sites and Occupied Spaces . W. J. T. Mitchell created in his previous works the key concepts which imply an approach to images as true objects of investigation – an “image science”. Author, continuing with his influential line of thoughts, amplifies interdisciplinary studies of visual media. The chapters also delve into such topics as conections between new media and architecture or the occupation of space in contemporary popular uprisings. Image science is a call for a method of studying images that overcomes the “two-culture split” between the natural and human sciences.